Pengaruh Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen (Studi Kasus PT. Sumber Alfaria Trijaya. Tbk/Alfamart) - Santuri Ramadhani (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2024)
Follow this template for guidelines for writing articles in the JES Journal. Articles submitted must use page dimensions (A4), margins on all sides (2.54vcm right, left, bottom; 2.54 cm top margin), type and font dimensions (Times New Roman 11 on the abstract and Times New Roman 11 on content section), procedures for placing tables and figures, procedures for writing table and figure names, procedures for writing references (referring to APA format), and other formats as exemplified or explained in this template. Write down the key words under the abstract, a maximum of 5 words and alphabetically alphabetize the first letter of each word.